1973
DOI: 10.1037/h0035398
|View full text |Cite
|
Sign up to set email alerts
|

Counselor power base, influence attempt, and behavior change in counseling.

Abstract: Gave a 30-min individual interview to 48 college males, all of whom described themselves as "procrastinators." The interview explored current and historical difficulties stemming from Ss' procrastination, and ended with an interviewer attempt to influence Ss to take some specific action on the procrastination issue of greatest current concern. 8 experimental conditions were defined by (a) the 2 interviews, (b) "expert" or "referent" roles, and (c) delivery of influence attempt in a manner congruent with the "e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 14 publications
4
57
0
Order By: Relevance
“…1963;Bergin, 1962). A number of analogue studies have shown therapist expertness to be positively correlated with the patient's choice of therapist 11 (Corrigan, 1978), levels of rated attraction and trustworthiness (Greenberg, 1969;McKee & Smouse, 1983), information re~all (Guttman & Haase, 1972), attitudinal change (Binderman, Fretz, Scott & Abrams, 1972;Bergin, 1962) and to both self reported and actual behavior change (Dell, 1973;Hoffman & Spencer, 1977). In one of a few naturalistic long term treatment studies, Beutler, et ale (1975) found that patients post hoc perceptions of therapist credibility were significantly and positively related to patient improvement.…”
Section: Credibilitymentioning
confidence: 99%
“…1963;Bergin, 1962). A number of analogue studies have shown therapist expertness to be positively correlated with the patient's choice of therapist 11 (Corrigan, 1978), levels of rated attraction and trustworthiness (Greenberg, 1969;McKee & Smouse, 1983), information re~all (Guttman & Haase, 1972), attitudinal change (Binderman, Fretz, Scott & Abrams, 1972;Bergin, 1962) and to both self reported and actual behavior change (Dell, 1973;Hoffman & Spencer, 1977). In one of a few naturalistic long term treatment studies, Beutler, et ale (1975) found that patients post hoc perceptions of therapist credibility were significantly and positively related to patient improvement.…”
Section: Credibilitymentioning
confidence: 99%
“…Strong and a number of his colleagues (Dell, 1973;Dell & Schmidt, 1976;, 1971Strong, 1968Strong, , 1970Strong, , 1978Strong & Dixon, 1971;Strong & Matross, 1973;Strong & Schmidt, 1970a, 1970b developed and empirically tested a two-stage model of helping based on social influence theory (a social psychological perspective). Stated simply, Stage I involves the establishment of a power or influence base for the counselor.…”
Section: Social Influence Rolesmentioning
confidence: 99%
“…When a referent power identification is made, the person will often strive to perceive and act in the manner of the individual or group agent (French & Raven, 1959), especially if there is correspondence between the need of the person and the resources of the agent (Dell, 1973). Thus, the more a person feels the need for understanding (or for a challenge, or for new coping techniques) and the better the need fits the profile of the referent individual or group, the greater the power of the peer referent agent.…”
mentioning
confidence: 99%